Building an Evidence-Based, Holistic Approach to Advancing Integrated Employment. (September 2018) - Hall, Allison Cohen; Butterworth, John; Winsor, Jean; Kramer, John; Nye-Lengerman, Kelly; Timmons, Jaimie
Since the introduction of supported employment in the Developmental Disabilities Act of 1984 and the Rehabilitation Act Amendments of 1986, there has been continued development and refinement of best practices in employment services and supports. Progress includes creative outcomes for individuals with significant support needs including customized jobs and self-employment, community rehabilitation providers that have shifted emphasis to integrated employment, and states that have made a substantial investment in Employment First policy and strategy. Despite these achievements, the promise of integrated employment remains elusive for the majority of individuals with intellectual and developmental disabilities. The number of individuals supported in integrated employment by state agencies has remained stagnant for the past 15 years, participation in nonwork services has grown rapidly, and individual employment supports have not been implemented with fidelity. This article presents preliminary findings from activities completed by the Rehabilitation Research and Training Center on Advancing Employment for Individuals with Intellectual and Developmental Disabilities and discusses a framework for organizing state and federal investments in research, practice, and systems change.